2018
DOI: 10.1002/pbc.27469
|View full text |Cite
|
Sign up to set email alerts
|

Salvage regimens for pediatric patients with relapsed nasopharyngeal carcinoma

Abstract: There is no established salvage regimen for pediatric patients with relapsed nasopharyngeal carcinoma (NPC) and outcomes are dismal. We performed a multicenter retrospective review to determine outcomes after first salvage therapy for pediatric patients with relapsed NPC. Fourteen patients were treated with varied regimens. Two of the 14 patients received oxaliplatin-containing regimens and achieved a long-term complete response. Although definitive recommendations cannot be made based on outcomes for 14 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…11 For pediatric patients with relapsed NPC, an oxaliplatin containing regimen in combination with gemcitabine is recommended as a reasonable choice for first line salvage therapy by DeRenzo et al He has reported a 3 year event free survival of 34% and overall survival of 44% in his study of 14 pediatric relapsed/ progressive NPC cases. 12 Currently no molecular targeted therapy has been approved for treatment of relapsed metastatic NPC. Immunotherapy has proven to be effective in few clinical trials but its use is still experimental.…”
Section: Discussionmentioning
confidence: 99%
“…11 For pediatric patients with relapsed NPC, an oxaliplatin containing regimen in combination with gemcitabine is recommended as a reasonable choice for first line salvage therapy by DeRenzo et al He has reported a 3 year event free survival of 34% and overall survival of 44% in his study of 14 pediatric relapsed/ progressive NPC cases. 12 Currently no molecular targeted therapy has been approved for treatment of relapsed metastatic NPC. Immunotherapy has proven to be effective in few clinical trials but its use is still experimental.…”
Section: Discussionmentioning
confidence: 99%
“…NPC is usually inoperable due to the complex anatomical location of the disease, and surgery of this primary neoplasm is confined to biopsy only. Radical neck dissection is considered if the primary tumour appears to be controlled or there are persistent neck nodes after chemoradiation or isolated recurrence in the neck after radiation [12]. Paediatric patients with NPC respond better than adult patients to treatment, and so the outcomes tend to be better.…”
Section: Discussionmentioning
confidence: 99%
“…However, no other studies in Other immune therapies are increasingly reported, mainly in adult NPC, but also in pediatric NPC, including the use of immune checkpoint inhibitors (ICI) and EBVspecific T cells, both showing promising responses, although these are mainly used in the setting of progressive or relapsed disease. [62][63][64][65][66][67][68][69][70]…”
Section: Maintenance Therapymentioning
confidence: 99%
“…Oxaliplatin-doxorubicin 67,75,76 4-6 y Alive at time of report Oxaliplatin-gemcitabine 67 20 mo Alive at time of report Carboplatin-gemcitabine-paclitaxel 67 7 mo 11 mo Carboplatin-docetaxel 67 4 mo 14 mo Carboplatin-5FU 67 15 mo 22 mo Carboplatin-paclitaxel-ifosfamide combined with EBV-specific lymphocytes 67 43 mo Alive at time of report Carboplatin-paclitaxel 67 3 mo Alive at time of report Doxorubicin-vincristine-cyclophosphamide-irinotecan combined with EBV-specific lymphocytes 67 49 mo Alive at time of report Nivolumab 67 12 mo Alive at time of report Gemcitabine-vinorelbine 67 2 mo 13 mo Cetuximab 67 7 mo 21 mo Irinotecan-topotecan 67 3 mo 17 mo Gemcitabine-docetaxel 13 75 mo Alive at time of report Carboplatin-ifosfamide-etoposide 77 7 mo 7 mo Carboplatine-5FU-docetaxel 18 2 y Alive at time of report EBV-CTLs+chemotherapy 78 NA NA Progress in both local and systemic treatments of pediatric NPC reduced the rates of local relapse in primary nonmetastatic disease, with recent reports showing failure of local control in 4% to 7%. 10,13,15,20,35,52 However, despite improved local control, rates of distant metastatic relapse have not significantly changed, with a distant failure rate of 10% to 13% reported in several national cohorts, reflecting the need for better systemic treatment for pediatric NPC.…”
Section: Salvage Treatment Efs Following Relapse Os Following Relapsementioning
confidence: 99%